Problems in Organizing the Economic Security System of Enterprises (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines the main problems faced by enterprises in the organization of the economic security system. The conditions for achieving economic security are presented through a comprehensive risk assessment.